Use of awake proning to avoid invasive ventilation in a patient with severe COVID-19 pneumonitis. Issue 8 (3rd August 2020) - Whittemore, Paul; Macfarlane, Laura; Herbert, Anna; Farrant, John
Abstract : A 60-year-old man with swab-positive COVID-19 and extensive ground-glass change seen on CT imaging was successfully managed on our COVID-19 high-dependency unit with only low-flow oxygen and strict awake proning instructions. He was successfully weaned off oxygen entirely without any requirement for non-invasive or invasive ventilation and made a recovery to be discharged home after an 18-day hospital stay.